Par-delà l’adéquationnisme méthodologique. Revisiter les médiations entre formation et emploi - Cédric Frétigné (Recherches en Éducation)
The text aims to analyse the ins and outs of a continual form of “methodological adequationnism” which still organize a part of the research and ever inform the public policies about training/employment joints. The first part accounts for the posterity of the adequationnism mind inside the brainworks led about training/employment relationships. It specifies how this mind is structuring of public policies of employment for unemployed. And describes the impasses and accounts for reasons for what politicians and public managers continue to refer. After that, two alternative approaches are detailed. Each other is focalised on the “professional socialization”. They try to keep out of the “methodological adequationnism”.